2013
DOI: 10.1177/0022487113494413
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Online and Face-to-Face Professional Development in the Context of Curriculum Implementation

Abstract: This study employed a randomized experiment to examine differences in teacher and student learning from professional development (PD) in two modalities: online and face-to-face. The study explores whether there are differences in teacher knowledge and beliefs, teacher classroom practice, and student learning outcomes related to PD modality. Comparison of classroom practice and student learning outcomes, normally difficult to establish in PD research, is facilitated by the use of a common set of curriculum mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(156 citation statements)
references
References 31 publications
11
136
1
8
Order By: Relevance
“…When designing collaboratively, teachers are enacting their capacity to initiate educational change. This active, agentive role on the part of the teachers, is consistent with literature on teacher professional development that suggests the active engagement of teachers over an extensive period (along with a focus on content, pedagogy and local context) as crucial for teacher learning (Fishman et al 2013;Garet et al 2001). By engaging teachers over an extended period in the collaborative design of curriculum materials, chances are increased that they will assume individual and collective responsibility, leading to intentional and transformative action and learning from the process.…”
Section: Agency In Collaborative Designsupporting
confidence: 83%
“…When designing collaboratively, teachers are enacting their capacity to initiate educational change. This active, agentive role on the part of the teachers, is consistent with literature on teacher professional development that suggests the active engagement of teachers over an extensive period (along with a focus on content, pedagogy and local context) as crucial for teacher learning (Fishman et al 2013;Garet et al 2001). By engaging teachers over an extended period in the collaborative design of curriculum materials, chances are increased that they will assume individual and collective responsibility, leading to intentional and transformative action and learning from the process.…”
Section: Agency In Collaborative Designsupporting
confidence: 83%
“…Although it has been reported that face-to-face interaction for adult learners has no advantage over blended learning [15], that is likely to be because the face-to-face elements of blended learning allow relationships to be established, in comparison to purely online training opportunities, such as MOOCs in computer science. Online learning courses may be better suited to certain domains: the "getting stuck" element of computer programming means that it becomes easy to give up when it becomes difficult [1].…”
Section: Communities Of Practice -Online and Offlinementioning
confidence: 99%
“…The e-learning framework enables large groups of students to be effectively managed (Garrison & Vaughn, 2008). However, Fishman et al (2013) point out, in their discussion of professional development for teachers, that planning and implementing effective programs involves substantial costs whether the learning platform is online or face-to-face. Whether online learning is the more cost effective option or not is dependent on the context in which the learning is taking place.…”
Section: Introductionmentioning
confidence: 99%